ANALYSIS OF THE FACTORS WHICH CAN AFFECT THE PRELOAD OF THE WHEEL BOLTED JOINT - QIAN HaiTing; RAO LiFang; HAN YuQi (Jixie qiangdu)
Wheel bolted joint,which is consisted of wheel,brake disc,bearing flange and the threaded fasteners which clamp the components,is a mechanical system. This paper discusses the clamp load of the wheel bolted joint,and takes the wheel and threaded fasteners as the research objectives. And this paper studies how the two components affect the clamp load of the joint. The result of this paper provides guidance to design a robust wheel bolted joint.